'The Untold Story': The mediated female ghost in England's Blenheim Palace. (February 2015) - Roberts, Robin
Designated a World Heritage site, Blenheim Palace demonstrates the use of technology and gender in tourist destinations to re-package cultural sites. A multi-media exhibit entitled 'The Untold Story' updates the site by using new media not to emphasize the great public triumphs, but instead to reveal private family relationships. Told by a projected apparition of the first Duchess' lady's maid, Grace Ridley, the exhibit addresses the tourists by including them in intimate, behind-the-scenes views of 300 years of family stories. The ghostly female narrator stands in for the tourist, a feminized outsider fascinated by the gossipy version of family history. Examining 'The Untold Story' provides insight into gender negotiations within tourist sites. This particular combination of new media and a female ghost exposes the emphasis in traditional heritage sites on elites, as well as anxiety about the estate's dependence on servants in the past and tourists in the present.